Financing Low-Carbon Transitions through Carbon Pricing and Green Bonds - Heine, Dirk (World Bank, Washington, DC, 2019)
To finance the transition to low-carbon economies required to mitigate climate change, countries are increasingly using a combination of carbon pricing and green bonds. This paper studies the reasoning behind such policy mixes and the economic interaction effects that result from these different policy instruments. The paper models these interactions using an inter-temporal model that proposes burden sharing between current and future generations. The issuance of green bonds helps to enable immediate investment in climate change mitigation and adaptation, and the bonds would be repaid by future generations in such a way that those who benefit from reduced future environmental damage share in the burden of financing the mitigation efforts undertaken today. The paper examines the effects of combining green bonds and carbon pricing in a three-phase model and uses a numerical solution procedure that allows for finite-horizon solutions and phase changes. The paper shows that green bonds perform better when they are combined with carbon pricing. The proposed policy option appears to be politically more feasible than a green transition based only on carbon pricing, and it is more prudent for debt sustainability than a green transition that relies overly on green bonds.